2010
DOI: 10.1128/aac.00945-09
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antifungal Therapy Timing on Mortality in Cancer Patients with Candidemia

Abstract: Prior studies have shown that delays in treatment are associated with increased mortality in patients with candidemia. The purpose of this study was to measure three separate time periods comprising the diagnosis and treatment of candidemia and to determine which one(s) is associated with hospital mortality. Patients with blood cultures positive for Candida spp. were identified. Subjects were excluded if no antifungal therapy was given or if there was preexisting antifungal therapy. Collected data included the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
1
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 48 publications
6
77
1
7
Order By: Relevance
“…Several studies have shown that early treatment improves overall survival (20,34,50). To our surprise, we were not able to detect any difference in outcome dependent on the timing of therapy.…”
Section: Discussioncontrasting
confidence: 81%
“…Several studies have shown that early treatment improves overall survival (20,34,50). To our surprise, we were not able to detect any difference in outcome dependent on the timing of therapy.…”
Section: Discussioncontrasting
confidence: 81%
“…For cancer patients with candidemia, the incubation length i.e. the time to a positive culture (median, 32.1 hours) is an independent risk factor for inhospital mortality, which increases an estimated 1.025-fold for every additional hour [Taur et al 2010]. The early use of diagnostic tests in the face of possible fungal infection can contribute to the early identification of IFI and initiation of antifungal therapy.…”
Section: Managementmentioning
confidence: 99%
“…Predictors of unfavorable outcome for IC include old age (>6065 years) [Hahn-Ast et al 2010;Horn et al 2010;Chen et al 2006;Uzun and Anaissie, 2000], the presence and persistence of neutropenia [Horn et al 2010;Uzun and Anaissie, 2000;Anaissie et al 1998], multiorgan yeast dissemination [Uzun and Anaissie, 2000;Anaissie et al 1998], corticosteroid therapy [Horn et al 2010;Labelle et al 2008;Chen et al 2006], high Acute Physiology and Chronic Health Evaluation (APACHE) II or III scores [Horn et al 2010;Labelle et al 2008;Anaissie et al 1998], and delayed treatment [Taur et al 2010;Garey et al 2006;Morrell et al 2005 [Uzun and Anaissie, 2000] are also associated with increased risk of death. In some studies removal of vascular catheters improved patient outcome [Horn et al 2010;Labelle et al 2008;Anaissie et al 1998], but in another study removal of vascular access devices was not associated with better outcome except for a subset of patients with device-related candidemia [Chen et al 2006].…”
Section: Prognosis Of Patients With Invasive Candidiasismentioning
confidence: 99%
“…Candida species are the 4th cause of nosocomial bloodstream infection and are associated with a high mortality rate (2). Many studies demonstrated that rapid initiation of appropriate antifungal therapy is crucial to reducing mortality (3,4). The susceptibility to antifungal molecules varies depending on the genus and the species.…”
mentioning
confidence: 99%